Assessment of Methicillin-Resistant Staphylococcus aureus (MRSA) knowledge and awareness among healthcare workers in South-Lebanon - Ali El Roz; Taghrid Chaaban; Hawraa Issa; José-Noel Ibrahim; Zeinab Ezzeddine; Ghassan Ghssein (Infection Prevention in Practice)
Summary: Background: Methicillin-Resistant Staphylococcus aureus (MRSA) is a well-known cause of hospital acquired infections (HAIs), associated with high rates of morbidity and mortality. In healthcare settings, MRSA can spread via contaminated surfaces and direct contact. Objective: This study aims to assess the knowledge and awareness of MRSA risks, prevention methods (such as hand hygiene), proper antibiotics use, and multidrug resistance among various groups of healthcare workers (HCWs) in Southern Lebanon. Methods: A total of 244 HCWs, including those in medical services (MS), paramedical services (PS), and non-medical services (NMS), were conveniently selected for this study. Data was gathered using a structured, validated questionnaire that explored their knowledge and awareness of MRSA risks, prevention measures, hand hygiene practices, and multidrug resistance. Results: The findings revealed that 68% of HCWs were aware of the origin of MRSA infection, and 61.5% and 51.6% were familiar with its treatment and transmission, respectively. Only 24.2% of HCWs were able to differentiate between hospital-acquired and community-acquired MRSA, 14.7% were aware of the institution's written MRSA control protocols, and 17.6% had heard of MRSA infections. Notably, knowledge and hand hygiene practices were significantly better among MS HCWs than PS and NMS groups (P<0.0001). While all HCWs were familiar with antibiotic usage and drug resistance, NMS HCWs were more likely to use antibiotics without a prescription compared to MS and PS groups (P<0.003). Conclusion: HCWs in South-Lebanon demonstrated a knowledge gap regarding MRSA risks and prevention guidelines. These findings underscore the need for targeted educational intervention on MRSA, as well as coordinated efforts by healthcare authorities and centres to control MRSA infections.